A pragmatic evaluation of a high-fidelity dialectical behaviour therapy programme for youth with borderline personality disorder. (4th May 2021) - Lakeman, R.; Emeleus, M.; Davies, S.; Anderson, S.
ABSTRACT: Objective: This paper describes and evaluates a high-fidelity Dialectical Behaviour Therapy (DBT) programme for youth (15–25 years). The project was undertaken as a partnership between public mental health services and a non-government organisation in regional Australia. DBT is an evidence-based treatment for Borderline Personality Disorder (BPD) but is rarely accessible within public mental health services. Method: Participants completed an Adverse Childhood Experiences (ACE) questionnaire, repeated measures of the Borderline Symptom List (BSL-23), supplementary behaviour questionnaire (BSL-Supp) and general well-being questionnaires. Hospital and emergency service use was examined for the year prior to referral to the programme and for the year following completion. The characteristics of those people who did not complete the programme were also described. Results: Borderline personality symptoms were correlated with the number of reported adverse childhood experiences. Participants who remained in the programme for at least twelve weeks had significant reductions in BSL-23 scores with several reporting no symptoms after completing the programme. Participants had high rates of hospital and emergency department use in the year before participation and significantly less use in the year following completion. Discussion: It is feasible to deliver a high fidelity DBT programme to youth in a regional centre in Australia and achieve reductions in symptoms and use of hospital and emergency services in a regional public mental health service. Abstract :